Empirical Economic and Financial Research - Theory, Methods and Practice

Introduction - Beran, Jan; Feng, Yuanhua; Hebbel, Hartmut (Empirical Economic and Financial Research)

An iterative plug-in algorithm for realized kernels - Feng, Yuanhua; Zhou, Chen

Uncertainty in Weighting Formulary Apportionment Factors. How Does Weighting Uncertainty Impact After-Tax Income of Multinational Groups?, - Ortmann, Regina
Formulary apportionment is an intensively debated mechanism for allocating tax base within multinational groups. Systems under which the formula is identical in all jurisdictions and systems under which jurisdictions can determine the weights on the formula factors individually can be observed. The latter systems produce uncertainty about the overall tax-liable share of the future group tax base. Counter-intuitively, I identify scenarios under which increased uncertainty leads to higher expected future group income. My results provide helpful insights for firms and policy makers debating the specific design of a formulary apportionment system.

Formula Apportionment or Separate Accounting? Tax-Induced Distortions of Multinationals' Locational Investment Decisions - Ortmann, Regina; Pummerer, Erich

Entscheidungskalküle US-amerikanischer Unternehmen bei Tax Inversions. What Drives the Decision of U.S. Firms to Expatriate? - Oßwald, Benjamin; Sureth-Sloane, Caren (Steuer und Wirtschaft International)

Investment Effects of Wealth Taxes under Uncertainty and Irreversibility - Niemann, Rainer; Sureth-Sloane, Caren

Hold or Sell? How Capital Gains Taxation Affects Holding Decisions - Hegemann, Annika; Kunoth, Angela; Rupp, Kristina; Sureth-Sloane, Caren

The Effect of Taxes on Corporate Financing Decision - Evidence from the German Interest Barrier - Alberternst, Stephan; Sureth-Sloane, Caren

Managing the bright and dark sides of status endowment in hierarchical loyalty programs - Eggert, Andreas; Steinhoff, Lena; Garnefeld, Ina (Journal of Service Research)

How sales strategy translates into performance: The role of salesperson customer orientation and value-based selling - Terho, Harri; Eggert, Andreas; Haas, Alexander; Ulaga, Wolfgang (Industrial Marketing Management)

Heading for new shores: Do service and hybrid innovations outperform product innovations in industrial companies? - Eggert, Andreas; Thiesbrummel, Christoph; Deutscher, Christian (Industrial Marketing Management)

"...and they are really lying: Clean Evidence on the Pervasiveness of Cheating in Professional Contexts from a Field Experiment" - Djawadi, Behnud Mir; Fahr, René (Journal of Economic Psychology)

Bank funding stability, pricing strategies and the guidance of depositors - Schlueter, Tobias; Sievers, Sönke; Hartmann-Wendels, Thomas (Journal of Banking & Finance (VHB-JOURQUAL 3 Ranking A))
Banks face a 'behavioralization' of their balance sheets since deposit funding increasingly consists of non-maturing deposits with uncertain cash flows exposing banks to asset liability (ALM) risk. Thus, this study examines the behavior of banks’ retail customers regarding non-maturing deposits. Our unique sample comprises the contract and cash flow data for 2.2 million individual contracts from 1991 to 2010. We find that contractual rewards, i.e., qualified interest payments, and government subsidies, effectively stabilize saving behavior and thus bank funding. The probability of an early deposit withdrawal decreases by approximately 40%, and cash flow volatility drops by about 25%. Our findings provide important insights for banks using pricing incentives to steer desired saving patterns for their non-maturing deposit portfolios. Finally, these results are informative regarding the bank liquidity regulations (Basel III) concerning the stability of deposits and the minimum requirements for risk management (European Commission DIRECTIVE 2006/48/EC).
Keywords: retail saving behavior; non-maturing deposits; deposit funding; contractual rewards; interest rate bonus; saving persistence; cash flow volatility

Robust Equilibria in Location Games - Buechel, Berno; Röhl, Nils (European Journal of Operational Research)
In the framework of spatial competition, two or more players strategically choose a locationin order to attract consumers. It is assumed standardly that consumers with the same favorite location fully agree on the ranking of all possible locations. To investigate the necessity of this questionable and restrictive assumption, we model heterogeneity in consumers’ distance perceptions by individual edge lengths of a given graph. A proﬁle of location choices is called a “robust equilibrium” if it is a Nash equilibrium in several games which diﬀer only by the consumers’ perceptions of distances. For a ﬁnite number of players and any distribution of consumers, we provide a full characterization of all robust equilibria and derive structural conditions for their existence. Furthermore, we discuss whether the classical observations of minimal diﬀerentiation and ineﬃciency are robust phenomena. Thereby, we ﬁnd strong support for an old conjecture that in equilibrium ﬁrms form local clusters.

Wertbasiertes Verkaufen auf Industriegütermärkten - Eggert, Andreas; Haas, Alexander; Ulaga, Wolfgang; Terho, Harri (Handbuch Business-to-Business-Marketing)

Public good provision in blended groups of partners and strangers - Grund, Christian; Harbring, Christine; Thommes, Kirsten (Economics Letters)

Behavioral spillovers from freeriding in multilevel interactions - Thommes, Kirsten; Vyrastekova, Jana; Akkerman, Agnes (Journal of Behavioral and Experimental Economics)

Instructional Design of Mobilities in Vocational Education - Background, Concepts and Experiences

Instructional Design of Mobilities in Vocational Education - Background, Concepts and Experiences